2022
DOI: 10.1096/fj.202101837r
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor deficiency predisposes to progressive renal disease

Abstract: Epidermal growth factor (EGF) is produced in the kidney by thick ascending limbs of the loop of Henle and by distal convoluted tubules (DCTs). Reduced urinary EGF levels have been associated with chronic kidney disease but it is not known whether physiological levels of EGF protect the kidney from progressive renal disease. Here, we show that EGF‐deficient mice on a mixed genetic background had increased urinary microalbumin, and a subset of these mice developed severe progressive renal disease with azotemia t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
1
1
Order By: Relevance
“…On the one hand, RNLS is an amine oxidase that regulates blood flow by metabolizing catecholamines and improves the injury caused by insufficient perfusion. In contrast, previous studies have shown that RNLS directly affects the function of renal tubular cells (49,50).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…On the one hand, RNLS is an amine oxidase that regulates blood flow by metabolizing catecholamines and improves the injury caused by insufficient perfusion. In contrast, previous studies have shown that RNLS directly affects the function of renal tubular cells (49,50).…”
Section: Discussioncontrasting
confidence: 69%
“…Renal tubules have the function of material transport, including reabsorption and secretion. Meanwhile, renal tubule epithelial cells can regulate renal function by secreting various factors ( 49 ). Our data suggested that the level of RNLS in DT and TAL was significantly increased after exercise, while the level of RNLS in renal tubular epithelial cells of cortex was lower than that of DT.…”
Section: Discussionmentioning
confidence: 99%
“… 30 A series of experimental studies have shown that EGF-deficient mice developed attenuation of the proximal tubular brush border and kidney fibrosis; in rats, EGF promotes kidney tubule cell regeneration, and it improves kidney function recovery after acute kidney injury. 30 , 31 , 32 In humans, kidney biopsy studies in patients with CKD have demonstrated that lower EGF mRNA expression correlates with greater tubulointerstitial injury, whereas higher urine EGF concentrations are indicative of functional kidney tubules and higher regeneration capability. 33 , 34 These findings, spanning from experimental animals to multiple human populations, directionally align with the results observed in this study.…”
Section: Discussionmentioning
confidence: 99%